Research of the investment environment and its basic requirements and challenges of the institutional sphere as an element of the methodology of strategic management of the development of stakeholder enterprises in the construction industry - Sibikovskyi, A.; Hura, Y.; Movchan, M.; Bodianskyi , O. (Ways to Improve Construction Efficiency, 2024)
The modern conditions of the construction industry require considering the investment environment as a key factor in the strategic management of stakeholder companies' development. The construction sector, being capital-intensive and long-term in implementation, necessitates a thorough analysis of the specifics of attracting investments, their structure, and mechanisms for adapting to dynamic market changes. Institutional aspects of shaping this environment play a central role in ensuring the sustainability of financial flows, effective resource allocation, and risk minimization. An important area of research is the identification of basic requirements for the institutional sphere that determine the competitiveness of the investment process. Regulatory mechanisms, legislative initiatives, investment guarantee systems, and financial instruments influence the effectiveness of capital attraction to the construction sector. Moreover, significant challenges arise due to the instability of the economic environment, changes in financing policies, technological transformations, and environmental standards. In this context, developing a methodological approach to strategic management of stakeholder companies' development becomes relevant, allowing not only to address contemporary challenges but also to create a stable model for their further growth. The formation of an effective investment environment is only possible through the integration of institutional mechanisms into the strategic management system. This involves developing models of partnership interaction between government structures, financial institutions, and construction companies, which will help reduce transaction costs and increase the transparency of investment processes. Furthermore, it is critically important to assess economic risks and implement compensation mechanisms through insurance, state support, and financial incentives. Considering these aspects, the study of the investment environment is complex and based on a systematic analysis of its structural elements. The institutional challenges accompanying the development of the construction market require appropriate methodological solutions aimed at creating favorable conditions for investment attraction. This will enhance the resilience of the construction industry, contribute to the long-term development of stakeholder companies, and enable the creation of an adaptive management system capable of responding to the challenges of a dynamic market.